An evaluation of the Cygnet parenting support programme for parents of children with autism spectrum conditions. (March 2016) - Stuttard, Lucy; Beresford, Bryony; Clarke, Susan; Beecham, Jennifer; Morris, Andy
Highlights: Cygnet is a psycho-educational intervention for parents of children with autism spectrum conditions. We compared outcomes for parents attending Cygnet to a waiting list comparator group. Parenting satisfaction was significantly improved for parents attending Cygnet . These parents also reported improved child behaviour. Improvements were maintained six-months post-intervention. Abstract: Parents of children on the autistic spectrum often struggle to understand the condition and, related to this, manage their child's behaviour. Cygnet is a parenting intervention which aims to help parents address these difficulties, consequently improving parenting confidence. It is widely used in the United Kingdom (UK). Despite this, there have been few evaluations. This paper reports a small-scale pragmatic evaluation of Cygnet as it was routinely delivered in two English cities. A non-randomised controlled study of outcomes for parents (and their children) was conducted. Data regarding intervention fidelity and delivery costs were also collected. Parents either attending, or waiting to attend, Cygnet were recruited (intervention group: IG, n = 35; comparator group: CG, n = 32). Parents completed standardised measures of child behaviour and parenting sense of competence pre- and post-intervention, and at three-month follow-up (matched time points for CG). Longer-term outcomes were measured for the IG. IG parents also set specific child behaviour goals. Typically, the programme was delivered as specified by the manual. Attending Cygnet was associated with significant improvements in parenting satisfaction and the specific child behaviour goals. Findings regarding other outcomes were equivocal and further evaluation is required. We conclude that Cygnet is a promising intervention for parents of children with autism in terms of, at least, some outcomes.